Some Haskell source code (see ref):
-- | Sequential application.
--
-- A few functors support an implementation of '<*>' that is more
-- efficient than the default one.
(<*>) :: f (a -> b) -> f a -> f b
(<*>) = liftA2 id
-- | Lift a binary function to actions.
--
-- Some functors support an implementation of 'liftA2' that is more
-- efficient than the default one. In particular, if 'fmap' is an
-- expensive operation, it is likely better to use 'liftA2' than to
-- 'fmap' over the structure and then use '<*>'.
liftA2 :: (a -> b -> c) -> f a -> f b -> f c
liftA2 f x = (<*>) (fmap f x)
Three things seem to be quite confusing to me:
1) (<*>) is defined in terms of liftA2, where liftA2 is defined in terms of (<*>). How does it work? I see no obvious "recursion-break" case...
2) id is an a -> a function. Why is it passed into liftA2 as an (a -> b -> c) function?
3) fmap id x always equals x, since functors must preserve appropriate identities. Thus (<*>) (fmap id x) = (<*>) (x) where x = f a - an a-typed functor itself (by the way, how can a-typifying of the functor can be explained from the pure category theory's point of view? functor is just a mapping between categories, it has no further "typification"... seems like it is better to say - "a container of type a with an (endo)functor defined for each instance of asummed category Hask of well-defined Haskell types). So (<*>) (f a) while by definition (<*>) expects f(a' -> b'): thus, the only way to make it work is to deliberately bound a to be an (a' -> b'). However when I run :t \x -> (<*>) (fmap id x) in the gchi, it spits out something mind-blowing: f (a -> b) -> f a -> f b - which I fail to explain.
Can someone step by step explain how does that work and why it even compiles?
P.S. Category theory terms, if needed, are welcome.
For question 1, you left out a very important piece of context.
class Functor f => Applicative f where
{-# MINIMAL pure, ((<*>) | liftA2) #-}
Those definitions you quoted belong to a class. That means instances can override them. Furthermore, the MINIMAL pragma says that in order to work, at least one of them must be overridden in the instance. So the breaking of the recursion happens whenever one is overridden in a particular instance. This is just like how the Eq class defines (==) and (/=) in terms of each other so that you only need to provide a definition for one in a hand-written instance.
For question two, a -> b -> c is shorthand for a -> (b -> c). So it unifies with (let's rename variables to avoid collision) d -> d as (b -> c) -> (b ->c). (tangentially, that's also the type of ($).)
For three - you're absolutely right. Keep simplifying!
\x -> (<*>) (fmap id x)
\x -> (<*>) x
(<*>)
So it shouldn't really be a surprise ghci gave you the type of (<*>) back, should it?
1) (<*>) is defined in terms of liftA2, where liftA2 is defined in terms of (<*>). How does it work? I see no obvious "recursion-break" case...
It's not recursion. In your instance of Applicative you can either define both of them or just one. If you define just (<*>) then liftA2 is defined from (<*>), and vice versa.
2) id is an a -> a function. Why is it passed into liftA2 as an (a -> b -> c) function?
Unification works as follows,
(<*>) :: f (a -> b) -> f a -> f b
(<*>) = liftA2 id
liftA2 :: (a -> b -> c) -> f a -> f b -> f c
id : u -> u
liftA2 : (a -> (b -> c) -> f a -> f b -> f c
------------------------------------------------------
u = a
u = b->c
id : (b->c) -> (b->c)
liftA2 : ((b->c) -> (b->c)) -> f (b->c) -> f b -> f c
------------------------------------------------------
liftA2 id : f (b->c) -> f b -> f c
3.
liftA2 :: (a -> b -> c) -> f a -> f b -> f c
liftA2 h x = (<*>) (fmap h x)
Renamed the first argument from f to h, to prevent confusion since f also shows in the type
h :: a -> (b -> c)
x :: f a
fmap :: (a -> d) -> f a -> f d
------------------------------
d = b -> c
h :: a -> (b->c)
x :: f a
fmap :: (a -> (b->c)) -> f a -> f (b->c)
----------------------------------------
fmap h x :: f (b -> c)
fmap h x :: f (b -> c)
(<*>) :: f (b -> c) -> f b -> f c
-------------------------------------
(<*>) fmap h x :: f b -> f c
Edit:
Consistency
To show the consistency of both formulas, first lets first rewrite liftA2 into something simpler. We can use the formula below to get rid of fmap and use only pure and <*>
fmap h x = pure h <*> x
and it's best to put all points in the definition. So we get,
liftA2 h u v
= (<*>) (fmap h u) v
= fmap h u <*> v
= pure h <*> u <*> v
So we want to check the consistency of,
u <*> v = liftA2 id u v
liftA2 h u v = pure h <*> u <*> v
For the first we need the property that pure id <*> u = u
u <*> v
= liftA2 id u v
= pure id <*> u <*> v
= u <*> v
For the second we need a property of liftA2. Properties of applicative are usually given in terms of pure and <*> so we need to derive it first. The required formula is derived from pure h <*> pure x = pure (h x).
liftA2 h (pure x) v
= pure h <*> pure x <*> v
= pure (h x) <*> v
= liftA2 (h x) v
This requires h : t -> a -> b -> c. The proof of consistency becomes,
liftA2 h u v
= pure h <*> u <*> v
= pure h `liftA2 id` u `liftA2 id` v
= liftA2 id (liftA2 id (pure h) u) v
= liftA2 id (liftA2 h u) v
= liftA2 h u v
1) (<*>) is defined in terms of liftA2, where liftA2 is defined in terms of (<*>). How does it work? I see no obvious "recursion-break" case...
Each instance is responsible for overriding at least one of the two. This is documented in a machine-readable way in the pragma at the top of the class:
{-# MINIMAL pure, ((<*>) | liftA2) #-}
This pragma announces that instance writers must define at least the pure function and at least one of the other two.
id is an a -> a function. Why is it passed into liftA2 as an (a -> b -> c) function?
If id :: a -> a, we can choose a ~ d -> e to get id :: (d -> e) -> d -> e. Traditionally, this particular specialization of id is spelled ($) -- maybe you've seen that one before!
3) ...
I don't... actually see any contradiction set up in the facts you state. So I'm not sure how to explain away the contradiction for you. However, you have a few infelicities in your notation that might be related to mistakes in your thinking, so let's talk about them briefly.
You write
Thus (<*>) (fmap id x) = (<*>) (x) where x = f a.
This is not quite right; the type of x is f a for some Functor f, but it is not necessarily equal to f a.
by the way, how can a-typifying of the functor can be explained from the pure category theory's point of view? functor is just a mapping between categories, it has no further "typification"... seems like it is better to say - "a container of type a with an (endo)functor defined for each instance of assumed category Hask of well-defined Haskell types
A functor constitutes two things: a mapping from objects to objects, and a mapping from arrows to arrows that is compatible with the object mapping. In a Haskell Functor instance declaration like
instance Functor F where fmap = fmapForF
the F is the mapping from objects to objects (objects in both the source and target categories are types, and F is a thing which takes a type and produces a type) and the fmapForF is the mapping from arrows to arrows.
I run :t \x -> (<*>) (fmap id x) in the gchi, it spits out something mind-blowing: f (a -> b) -> f a -> f b - which I fail to explain.
Well, you already observed that fmap id x = x, which means \x -> (<*>) (fmap id x) = \x -> (<*>) x. And for any function f, f = \x -> f x (up to some niggles that aren't important right now), so in particular \x -> (<*>) (fmap id x) = (<*>). So ghci gives you the type of (<*>), as it should.
Here I have to disagree with the GHC devs on their coding style :)
I would like to argue that one should never write
ap = liftA2 id
but, instead, use the equivalent
ap = liftA2 ($)
since the latter makes it clear that we are lifting the application operation.
(Actually, for very technical reasons GHC devs can not use $ here in this internal module, as pointed out below in the comments. So, at least they have a very good reason for their choice.)
Now, you might wonder why id can be used instead of $. Formally, we have
($) f x
= f x
= (id f) x
= id f x
hence, eta-contracting x then f, we get ($) = id.
Indeed, ($) is a "special case" of id.
id :: a -> a
-- choose a = (b -> c) as a special case
id :: (b -> c) -> (b -> c)
id :: (b -> c) -> b -> c
($):: (b -> c) -> b -> c
Hence, the main difference is: id is the identity on any type a, while ($) is the "identity" on any functional type b -> c. The latter is best visualized as a binary function (application), but it can equivalently be considered a unary function (identity) on a function type.
Related
Applicatives are often presented as a way to lift multi-argument functions
into a functor and apply functor values to it. But I wonder if there is some
subtle additional power stemming from the fact that it can do so by lifting
functions that return a function and applying the function arguments one at
a time.
Imagine instead we define an interface based on lifting functions whose argument is a tuple of arguments:
# from Functor
fmap :: (a -> b) -> Fa -> Fb
# from Applicative
pure :: a -> Fa
# combine multiple functor values into a functor of a tuple
tuple1 :: Fa -> F(a)
tuple2 :: Fa -> Fb -> F(a,b)
tuple3 :: Fa -> Fb -> Fc -> F(a,b,c)
(etc ...)
# lift multi-argument functions (that take a tuple as input)
ap_tuple1 :: ((a) -> b) -> F(a) -> Fb
ap_tuple2 :: ((a,b) -> c) -> F(a,b) -> Fc
ap_tuple3 :: ((a,b,c) -> d) -> F(a,b,c) -> Fd
(etc ..)
Assume we had the corresponding tuple function defined for every sized tuple we may encounter.
Would this interface be equally as powerful as the Applicative interface, given it allows for
lifting/applying-to multi-argument functions BUT doesn't allow for lifting/applying-to functions
that return a function? Obviously one can curry functions that take a tuple as an argument
so they can be lifted in an applicative and one can uncurry functions that return a function
in order to lift them into hypothetical implementation above. But to my mind there is a subtle
difference in power. Is there any difference? (Assuming the question even makes sense)
You've rediscovered the monoidal presentation of Applicative. It looks like this:
class Functor f => Monoidal f where
(>*<) :: f a -> f b -> f (a, b)
unit :: f ()
It's isomorphic to Applicative via:
(>*<) = liftA2 (,)
unit = pure ()
pure x = x <$ unit
f <*> x = fmap (uncurry ($)) (f >*< x)
By the way, your ap_tuple functions are all just fmap. The "hard" part with multiple values is combining them together. Splitting them back into pieces is "easy".
Yes, this is equally as powerful. Notice that pure and tuple1 are the same. Further, everything higher than tuple2 is recovered from tuple2 and fmap:
tuple3 x y z = repair <$> tuple2 (tuple2 x y) z
where repair ((a, b), c) = (a, b, c)
tuple4 w x y z = repair <$> tuple2 (tuple2 x y) (tuple2 x y)
where repair ((a, b), (c, d)) = (a, b, c, d)
-- etc.
Also, all of the ap_tuples are just fmap:
ap_tuple1 = fmap
ap_tuple2 = fmap
ap_tuple3 = fmap
-- ...
Renaming prod = tuple2, your question boils down to
Is
class Functor f => Applicative f where
pure :: a -> f a
prod :: f a -> f b -> f (a, b)
equivalent to
class Functor f => Applicative f where
pure :: a -> f a
liftA2 :: (a -> b -> c) -> f a -> f b -> f c
?
And you might already see that the answer is yes. prod is just a specialization of liftA2
prod = liftA2 (,)
But (,) is "natural" in the sense that it doesn't "delete" anything, so you can recover liftA2 just by destructuring the data back out:
liftA2 f x y = f' <$> prod x y
where f' (a, b) = f a b
I would like to combine the various lifts into a single class
class Lift a b where
lift :: a -> b
So that lift can be used in place of fmap, liftA2, liftA3, etc.
Now it is easy enough to write the instances for these:
instance Functor f => Lift (a -> b) (f a -> f b) where
lift = fmap
instance Applicative f => Lift (a -> b -> c) (f a -> f b -> f c) where
lift = liftA2
instance Applicative f => Lift (a -> b -> c -> d) (f a -> f b -> f c -> f d) where
lift = liftA3
However for liftA2 and beyond there is an inductive property. That is we can derive a lift from smaller lifts. For example:
liftA2 f a b = (liftA f a) <*> b
liftA3 f a b c = (liftA2 f a b) <*> c
liftA4 f a b c d = (liftA3 f a b c) <*> d
liftA5 f a b c d e = (liftA4 f a b c d) <*> e
...
So I would like to instead of enumerating each lift as a separate instances use induction to make all of them. However while the definition is inductive I have trouble expressing the relationship between one lift and the next algebraically. That is while I can describe it, it is not a combination of lifts and simple combinators.
Even if I rewwrite them point free we can see that each level is more complex that the last:
liftA2 = ((<*>) .) . liftA
liftA3 = (((<*>) .) .) . liftA2
liftA4 = ((((<*>) .) .) .) . liftA3
liftA5 = (((((<*>) .) .) .) .) . liftA4
...
Now I think that this could be worked around by adding a ghc natural to the class
class Lift (n :: Nat) (a :: Type) (b :: Type) | a b -> n where
lift :: a -> b
And then using a supporting type class to do a lot of the connective work. However this solution would be far from elegant and I view it mostly as a last resort since I would rather no bloat the class with a Nat used only for computation.
Is there a way I inductively define lift without changing the class definition like this?
I came across this discussion on the Haskell mailing list. From the discussion, there seems to be performance implications with adding liftA2 as a method of Applicative. Can you provide concrete examples why it is necessary to add liftA2 to Applicative methods?
The email is written in 2017. At that time the Applicative typeclass looked like:
class Functor f => Applicative f where
-- | Lift a value.
pure :: a -> f a
-- | Sequential application.
(<*>) :: f (a -> b) -> f a -> f b
-- | Sequence actions, discarding the value of the first argument.
(*>) :: f a -> f b -> f b
a1 *> a2 = (id <$ a1) <*> a2
-- This is essentially the same as liftA2 (const id), but if the
-- Functor instance has an optimized (<$), we want to use that instead.
-- | Sequence actions, discarding the value of the second argument.
(<*) :: f a -> f b -> f a
(<*) = liftA2 const
So without the liftA2 as part of the Applicative typeclass. It was defined as [src]:
liftA2 :: Applicative f => (a -> b -> c) -> f a -> f b -> f c
liftA2 f a b = fmap f a <*> b
so one could not make a special implementation in the typeclass. This means that sometimes liftA2 can be implemented more efficiently, but one can not define that.
For example the Maybe functor and Applicative are implemented as:
instance Functor Maybe where
fmap f (Just x) = Just (f x)
fmap _ Nothing = Nothing
instance Applicative Maybe where
pure = Just
Just f <*> Just x = Just (f x)
_ <*> _ = Nothing
This thus means that the liftA2 for a Maybe is implemented similar to:
liftA2Maybe :: (a -> b -> c) -> Maybe a -> Maybe b -> Maybe c
liftA2Maybe f x y = apMaybe (fmapMaybe f x) y
where fmapMaybe f (Just x) = Just (f x)
fmapMaybe _ Nothing = Nothing
apMaybe (Just f) (Just x) = Just (f x)
apMaybe _ _ = Nothing
But this is not optimal. It means that fmapMaybe will inspect if the parameter is a Just x, or Nothing, and then return a Just (f x) or a Nothing. But regardless, apMaybe will again inspect that, whereas we can already know that in advance. We can make a more efficient implementation with:
liftA2Maybe :: (a -> b -> c) -> Maybe a -> Maybe b -> Maybe c
liftA2Maybe f (Just x) (Just y) = Just (f x y)
liftA2Maybe _ _ _ = Nothing
here we avoid extra unpacking of data constructors. This is not that problematic however. For certain data structures like a ZipList the overhead will be more severe because the number of objects is larger.
On June 23, 2017, a new base library was published where the liftA2 function was added as a method to the Applicative type class.
class Applicative f => Monad f where
return :: a -> f a
(>>=) :: f a -> (a -> f b) -> f b
(<*>) can be derived from pure and (>>=):
fs <*> as =
fs >>= (\f -> as >>= (\a -> pure (f a)))
For the line
fs >>= (\f -> as >>= (\a -> pure (f a)))
I am confused by the usage of >>=. I think it takes a functor f a and a function, then return another functor f b. But in this expression, I feel lost.
Lets start with the type we're implementing:
(<*>) :: Monad f => f (a -> b) -> f a -> f b
(The normal type of <*> of course has an Applicative constraint, but here we're trying to use Monad to implement Applicative)
So in fs <*> as = _, fs is an "f of functions" (f (a -> b)), and as is an "f of as".
We'll start by binding fs:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= _
If you actually compile that, GHC will tell us what type the hole (_) has:
foo.hs:4:12: warning: [-Wtyped-holes]
• Found hole: _ :: (a -> b) -> f b
Where: ‘a’, ‘f’, ‘b’ are rigid type variables bound by
the type signature for:
(Main.<*>) :: forall (f :: * -> *) a b.
Monad f =>
f (a -> b) -> f a -> f b
at foo.hs:2:1-45
That makes sense. Monad's >>= takes an f a on the left and a function a -> f b on the right, so by binding an f (a -> b) on the left the function on the right gets to receive an (a -> b) function "extracted" from fs. And provided we can write a function that can use that to return an f b, then the whole bind expression will return the f b we need to meet the type signature for <*>.
So it'll look like:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> _)
What can we do there? We've got f :: a -> b, and we've still got as :: f a, and we need to make an f b. If you're used to Functor that's obvious; just fmap f as. Monad implies Functor, so this does in fact work:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> fmap f as)
It's also, I think, a much easier way to understand the way Applicative can be implemented generically using the facilities from Monad.
So why is your example written using another >>= and pure instead of just fmap? It's kind of harkening back to the days when Monad did not have Applicative and Functor as superclasses. Monad always "morally" implied both of these (since you can implement Applicative and Functor using only the features of Monad), but Haskell didn't always require there to be these instances, which leads to books, tutorials, blog posts, etc explaining how to implement these using only Monad. The example line given is simply inlining the definition of fmap in terms of >>= and pure (return)1.
I'll continue to unpack as if we didn't have fmap, so that it leads to the version you're confused by.
If we're not going to use fmap to combine f :: a -> b and as :: f a, then we'll need to bind as so that we have an expression of type a to apply f to:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> as >>= (\a -> _))
Inside that hole we need to make an f b, and we have f :: a -> b and a :: a. f a gives us a b, so we'll need to call pure to turn that into an f b:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> as >>= (\a -> pure (f a)))
So that's what this line is doing.
Binding fs :: f (a -> b) to get access to an f :: a -> b
Inside the function that has access to f it's binding as to get access to a :: a
Inside the function that has access to a (which is still inside the function that has access to f as well), call f a to make a b, and call pure on the result to make it an f b
1 You can implement fmap using >>= and pure as fmap f xs = xs >>= (\x -> pure (f x)), which is also fmap f xs = xs >>= pure . f. Hopefully you can see that the inner bind of your example is simply inlining the first version.
Applicative is a Functor. Monad is also a Functor. We can see the "Functorial" values as standing for computations of their "contained" ⁄ produced pure values (like IO a, Maybe a, [] a, etc.), as being the allegories of ⁄ metaphors for the various kinds of computations.
Functors describe ⁄ denote notions ⁄ types of computations, and Functorial values are reified computations which are "run" ⁄ interpreted in a separate step which is thus akin to that famous additional indirection step by adding which, allegedly, any computational problem can be solved.
Both fs and as are your Functorial values, and bind ((>>=), or in do notation <-) "gets" the carried values "in" the functor. Bind though belongs to Monad.
What we can implement in Monad with (using return as just a synonym for pure)
do { f <- fs ; -- fs >>= ( \ f -> -- fs :: F (a -> b) -- f :: a -> b
a <- as ; -- as >>= ( \ a -> -- as :: F a -- a :: a
return (f a) -- return (f a) ) ) -- f a :: b
} -- :: F b
( or, with MonadComprehensions,
[ f a | f <- fs, a <- as ]
), we get from the Applicative's <*> which expresses the same computation combination, but without the full power of Monad. The difference is, with Applicative as is not dependent on the value f there, "produced by" the computation denoted by fs. Monadic Functors allow such dependency, with
[ bar x y | x <- xs, y <- foo x ]
but Applicative Functors forbid it.
With Applicative all the "computations" (like fs or as) must be known "in advance"; with Monad they can be calculated -- purely -- based on the results of the previous "computation steps" (like foo x is doing: for (each) value x that the computation xs will produce, new computation foo x will be (purely) calculated, the computation that will produce (some) y(s) in its turn).
If you want to see how the types are aligned in the >>= expressions, here's your expression with its subexpressions named, so they can be annotated with their types,
exp = fs >>= g -- fs >>=
where g f = xs >>= h -- (\ f -> xs >>=
where h x = return (f x) -- ( \ x -> pure (f x) ) )
x :: a
f :: a -> b
f x :: b
return (f x) :: F b
h :: a -> F b -- (>>=) :: F a -> (a -> F b) -> F b
xs :: F a -- xs h
-- <-----
xs >>= h :: F b
g f :: F b
g :: (a -> b) -> F b -- (>>=) :: F (a->b) -> ((a->b) -> F b) -> F b
fs :: F (a -> b) -- fs g
-- <----------
fs >>= g :: F b
exp :: F b
and the types of the two (>>=) applications fit:
(fs :: F (a -> b)) >>= (g :: (a -> b) -> F b)) :: F b
(xs :: F a ) >>= (h :: (a -> F b)) :: F b
Thus, the overall type is indeed
foo :: F (a -> b) -> F a -> F b
foo fs xs = fs >>= g -- foo = (<*>)
where g f = xs >>= h
where h x = return (f x)
In the end, we can see monadic bind as an implementation of do, and treat the do notation
do {
abstractly, axiomatically, as consisting of the lines of the form
a <- F a ;
b <- F b ;
......
n <- F n ;
return (foo a b .... n)
}
(with a, F b, etc. denoting values of the corresponding types), such that it describes the overall combined computation of the type F t, where foo :: a -> b -> ... -> n -> t. And when none of the <-'s right-hand side's expressions is dependent on no preceding left-hand side's variable, it's not essentially Monadic, but just an Applicative computation that this do block is describing.
Because of the Monad laws it is enough to define the meaning of do blocks with just two <- lines. For Functors, just one <- line is allowed ( fmap f xs = do { x <- xs; return (f x) }).
Thus, Functors/Applicative Functors/Monads are EDSLs, embedded domain-specific languages, because the computation-descriptions are themselves values of our language (those to the right of the arrows in do notation).
Lastly, a types mandala for you:
T a
T (a -> b)
(a -> T b)
-------------------
T (T b)
-------------------
T b
This contains three in one:
F a A a M a
a -> b A (a -> b) a -> M b
-------------- -------------- -----------------
F b A b M b
You can define (<*>) in terms of (>>=) and return because all monads are applicative functors. You can read more about this in the Functor-Applicative-Monad Proposal. In particular, pure = return and (<*>) = ap is the shortest way to achieve an Applicative definition given an existing Monad definition.
See the type signatures for (<*>), ap and (>>=):
(<*>) :: Applicative f => f (a -> b) -> f a -> f b
ap :: Monad m => m (a -> b) -> m a -> m b
(>>=) :: Monad m => m a -> (a -> m b) -> m b
The type signature for (<*>) and ap are nearly equivalent. Since ap is written using do-notation, it is equivalent to some use of (>>=). I'm not sure this helps, but I find the definition of ap readable. Here's a rewrite:
ap m1 m2 = do { x1 <- m1; x2 <- m2; return (x1 x2) }
≡ ap m1 m2 = do
x1 <- m1
x2 <- m2
return (x1 x2)
≡ ap m1 m2 =
m1 >>= \x1 ->
m2 >>= \x2 ->
return (x1 x2)
≡ ap m1 m2 = m1 >>= \x1 -> m2 >>= \x2 -> return (x1 x2)
≡ ap mf ma = mf >>= (\f -> ma >>= (\a -> pure (f a)))
Which is your definition. You could show that this definition upholds the applicative functor laws, since not everything defined in terms of (>>=) and return does that.
I am reading in the haskellbook about applicative and trying to understand it.
In the book, the author mentioned:
So, with Applicative, we have a Monoid for our structure and function
application for our values!
How is monoid connected to applicative?
Remark: I don't own the book (yet), and IIRC, at least one of the authors is active on SO and should be able to answer this question. That being said, the idea behind a monoid (or rather a semigroup) is that you have a way to create another object from two objects in that monoid1:
mappend :: Monoid m => m -> m -> m
So how is Applicative a monoid? Well, it's a monoid in terms of its structure, as your quote says. That is, we start with an f something, continue with f anotherthing, and we get, you've guessed it a f resulthing:
amappend :: f (a -> b) -> f a -> f b
Before we continue, for a short, a very short time, let's forget that f has kind * -> *. What do we end up with?
amappend :: f -> f -> f
That's the "monodial structure" part. And that's the difference between Applicative and Functor in Haskell, since with Functor we don't have that property:
fmap :: (a -> b) -> f a -> f b
-- ^
-- no f here
That's also the reason we get into trouble if we try to use (+) or other functions with fmap only: after a single fmap we're stuck, unless we can somehow apply our new function in that new structure. Which brings us to the second part of your question:
So, with Applicative, we have [...] function application for our values!
Function application is ($). And if we have a look at <*>, we can immediately see that they are similar:
($) :: (a -> b) -> a -> b
(<*>) :: f (a -> b) -> f a -> f b
If we forget the f in (<*>), we just end up with ($). So (<*>) is just function application in the context of our structure:
increase :: Int -> Int
increase x = x + 1
five :: Int
five = 5
increaseA :: Applicative f => f (Int -> Int)
increaseA = pure increase
fiveA :: Applicative f => f Int
fiveA = pure 5
normalIncrease = increase $ five
applicativeIncrease = increaseA <*> fiveA
And that's, I guessed, what the author meant with "function application". We suddenly can take those functions that are hidden away in our structure and apply them on other values in our structure. And due to the monodial nature, we stay in that structure.
That being said, I personally would never call that monodial, since <*> does not operate on two arguments of the same type, and an applicative is missing the empty element.
1 For a real semigroup/monoid that operation should be associative, but that's not important here
Although this question got a great answer long ago, I would like to add a bit.
Take a look at the following class:
class Functor f => Monoidal f where
unit :: f ()
(**) :: f a -> f b -> f (a, b)
Before explaining why we need some Monoidal class for a question about Applicatives, let us first take a look at its laws, abiding by which gives us a monoid:
f a (x) is isomorphic to f ((), a) (unit ** x), which gives us the left identity. (** unit) :: f a -> f ((), a), fmap snd :: f ((), a) -> f a.
f a (x) is also isomorphic f (a, ()) (x ** unit), which gives us the right identity. (unit **) :: f a -> f (a, ()), fmap fst :: f (a, ()) -> f a.
f ((a, b), c) ((x ** y) ** z) is isomorphic to f (a, (b, c)) (x ** (y ** z)), which gives us the associativity. fmap assoc :: f ((a, b), c) -> f (a, (b, c)), fmap assoc' :: f (a, (b, c)) -> f ((a, b), c).
As you might have guessed, one can write down Applicative's methods with Monoidal's and the other way around:
unit = pure ()
f ** g = (,) <$> f <*> g = liftA2 (,) f g
pure x = const x <$> unit
f <*> g = uncurry id <$> (f ** g)
liftA2 f x y = uncurry f <$> (x ** y)
Moreover, one can prove that Monoidal and Applicative laws are telling us the same thing. I asked a question about this a while ago.